2019
DOI: 10.1021/acs.macromol.9b00953
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Chain Orientation of Aromatic Polyimides Evolved during Thermal Imidization from Shear-Oriented Glassy Liquid Crystalline Precursors

Abstract: A series of poly­(amic ester)­s, PMm, based on pyromellitic acid derivatives with long n-alkylene side chains [−(CH2) m H], were synthesized to prepare low-temperature lyotropic liquid crystalline (LC) precursors for a fully aromatic rigid-rod polyimide (PI). Highly oriented LC precursor films (m > 8) were prepared by shearing at ambient temperature. Although the polydispersity of PMm was not controlled, the PMm solution exhibited a lyotropic smectic phase in which the main chains were parallel to the layer no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Recently, Ishige et al found that concentrated solutions of polyamide esters exhibit a lyotropic-smectic phase and that the layer structure of this phase grows stepwise from a hydrophobic surface. 19,20) They developed a method for preparing vertically orientated aromatic polyimide thin films that utilize this phenomenon. 21) The orientation control utilizing the liquid crystalline phase has also been reported for small-molecule organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ishige et al found that concentrated solutions of polyamide esters exhibit a lyotropic-smectic phase and that the layer structure of this phase grows stepwise from a hydrophobic surface. 19,20) They developed a method for preparing vertically orientated aromatic polyimide thin films that utilize this phenomenon. 21) The orientation control utilizing the liquid crystalline phase has also been reported for small-molecule organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely used methods for producing amorphous polymers consisting of cyclic units is the cationic cyclization of unsaturated hydrocarbon polymers under acidic conditions via carbocationic intermediates. Kamigaito and co-workers reported that styrene–diene copolymer can be treated with strong Brönsted acid (CF 3 SO 3 H) to induce Friedel–Crafts alkylation between adjacent diene–styrene units to form a rigid tetrahydronaphthyl bicyclic main-chain structure. This intramolecular cyclization in the main chain leads to a high T g and robust mechanical properties for the random copolymer. The synthesis of thermally and optically high-performance plastics from styrene (St) and isoprene (Ip) through the intramolecularly cyclized random St-Ip polymers have been studied. Furthermore, postpolymerization modification reactions that change the main-chain structures of existing polymers can lead to new applications. …”
Section: Introductionmentioning
confidence: 99%